2018
DOI: 10.1007/s11214-018-0563-9
|View full text |Cite
|
Sign up to set email alerts
|

Pre-mission InSights on the Interior of Mars

Abstract: The Interior exploration using Seismic Investigations, Geodesy, and Heat Transport (InSight) Mission will focus on Mars' interior structure and evolution. The basic structure of crust, mantle, and core form soon after accretion. Understanding the early differentiation process on Mars and how it relates to bulk composition is key to improving our understanding of this process on rocky bodies in our solar system, as well as in other solar B S.E. Smrekar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 99 publications
(155 citation statements)
references
References 350 publications
(411 reference statements)
6
148
1
Order By: Relevance
“…Though all harmonic degrees and orders will be considered, the largest contributor is for the C 20 term. The predicted contribution to the observed value for this harmonic is provided in Table for several density profiles that were employed in Smrekar et al (). As is seen, depending on the assumed density profile, between 4.4% and 6.4% of the observed C 20 gravity coefficient is a result of hydrostatic interfaces beneath the lithosphere.…”
Section: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Though all harmonic degrees and orders will be considered, the largest contributor is for the C 20 term. The predicted contribution to the observed value for this harmonic is provided in Table for several density profiles that were employed in Smrekar et al (). As is seen, depending on the assumed density profile, between 4.4% and 6.4% of the observed C 20 gravity coefficient is a result of hydrostatic interfaces beneath the lithosphere.…”
Section: Applicationsmentioning
confidence: 99%
“…For our first test, we make use of a density profile of Mars that is derived from the Mars bulk-silicate compositional model of Taylor (2013). This model (TAAK, see Table 4) has a core radius of 1,791 km and is taken from the Mars reference models presented in Smrekar et al (2019). The predicted hydrostatic flattening corresponds to a difference of 17 km between the poles and equator, and the observed values of h 20 and h 40 , our predicted values, and those predicted by the first-and second-order hydrostatic theories from the numerical code of Chambat et al (2010) are given in Table 1. Somewhat remarkably, our first-order results and the second-order results using the code of Chambat et al (2010) for the zonal degree-2 surface shape h 20 are found to differ by only 0.09%.…”
Section: Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates a lunar bulk concentration of heat producing elements similar to that of the Earth. Present-day Martian heat flow is estimated to be 14-25 mW m −2 (Plesa et al, 2015(Plesa et al, , 2018Parro et al, 2017;Smrekar et al, 2019), in between the lunar and terrestrial values. Present-day Martian heat flow is estimated to be 14-25 mW m −2 (Plesa et al, 2015(Plesa et al, , 2018Parro et al, 2017;Smrekar et al, 2019), in between the lunar and terrestrial values.…”
Section: Introductionmentioning
confidence: 96%